Philosophical Legal Review on The Implementation of the Rights of the Child for Youth Offender Associated with Terrorism Case in Indonesia - Indah Pangestu Amaritasari (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2022)
Terrorism has been qualified as a serious crime in Indonesia. The gravity of the crime can be estimated based on the fact that a person accused of such an offence is classified as a high-risk offender. However, complications arise when children and/or youth are suspected of this crime. Indonesia has ratified international human rights instruments, including the Convention on the Rights of the Child. The question emerges on how the rights can be exercised when youth is suspected to commit such high-degree crime. There are some laws that must be taken into account for further analysis in relation to this issue, especially the Law on Juveniles Justice System and the Terrorism Law. The context of how these laws intersect with the implementation of the Rights of the Child is important to be considered for the best interest of the child, including their comprehensive rehabilitation and reintegration process. The philosophical legal approach used in this research aims to have comprehensive analysis and solution of the complexity associated with the implementation of the rights of the children associated with a terrorism charge, especially when it comes to the legal system. It is also of critical importance to identify possibilities of improvement in the implementation of these rights.